2011
DOI: 10.1007/s12594-011-0028-1
|View full text |Cite
|
Sign up to set email alerts
|

Paleobiogeography, Paleoecology and Paleoenvironmental Significance of the Cambrian Trilobites from the Zanskar Region (Zanskar-Spiti-Kinnaur Basin), Northwest Himalaya

Abstract: In present study the newly recorded latest Middle Cambrian trilobite fauna from the Cambrian succession of the Zanskar region of Zanskar-Spiti-Kinnaur Basin (Tethyan Himalaya) is analyzed critically to assess relationships with other Cambrian faunal elements of equatorial peri-Gondwanaland. The identification of genus Neoanomocarella, Parablackwelderia, Kunmingaspis, Fuchouia, Damesella and Dorypyge from the Cambrian of the Zanskar region and their comparison with those of South China and Australia is signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…The lack of a registered effect on their distribution along the platformtransect is certainly due to a lack of determination at the species level. Indeed, previous studies have demonstrated that the setting is important to the species-specific distribution of trilobites (Gaines and Droser, 2003;Amati, 2004;Singh, 2011).…”
Section: Influence Of Environmental Factors In the Distribution Of MImentioning
confidence: 99%
“…The lack of a registered effect on their distribution along the platformtransect is certainly due to a lack of determination at the species level. Indeed, previous studies have demonstrated that the setting is important to the species-specific distribution of trilobites (Gaines and Droser, 2003;Amati, 2004;Singh, 2011).…”
Section: Influence Of Environmental Factors In the Distribution Of MImentioning
confidence: 99%